USING MNEMONIC DEVICE STRATEGY TO MOTIVATE STUDENTS IN LEARNING ENGLISH VOCABULARY - Sudirman; Tawali (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
This research was aimed to describe whether Strategy Mnemonic Device can improve students’ motivation in learning English vocabulary or not. This research was a Classroom Action Research (CAR). The data obtained in the form of quantitative and qualitative ways. The instrument used by the researcher ware test (post-test) in the form of multiple choice and non-test in the form of a questionnaire. There were four steps in conducting: planning, action, observation, and reflection. This classroom action research was done in one cycle. The cycle was conducted into four meeting with recount text and mnemonics as the topic of discussion. The result of this study showed that students' improvement in mastering vocabulary was statistically significant. Based on the research conducted, the researcher found the significant improvement in the cycle, it could be seen from the mean of cycle which was 77,34 for pre - test and 84,65 for post-test. So, Strategy Mnemonic Device was able to improve students’ motivation in learning English vocabulary. Through this strategy students have the opportunity to work together in groups and help each other. Hopefully, this strategy helped the students more motivation to learning the vocabulary mastery.